Wpływ cyrkulacji atmosferycznej na występowanie dni z burzą w Poznaniu w latach 1951-2000 - Kolendowicz, Leszek (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
The study concerns research into the connection between atmospheric circulation over the area of Central and Eastern Europe, and the occurrence of days with thunderstorms in Poznań (Poland). The analysis of lower synoptic maps for the researched period 1951–2000 made it possible to isolate seven types of synoptic situations characteristic of days with thunderstorms on the area of Poland. During research based on the use of logistic regression, a determination was made of the influence of various synoptic situation types on thunderstorm activity in one of the polish meteorological station – Poznań. An indication was made of type 2 of synoptic situations that is particularly conducive to the appearance of days with thunderstorms. This type is also characterised by the highest probability of the occurrence of stormy days. It has to be pointed out that type 2 synoptic situation may be the cause of very violent storms not only in Poland, but also in Europe or the USA. This is reflected in the descriptions of individual cases of violent storms or their accompanying phenomena occurring over Europe (PIAGET 1976; COURVOISIER et al. 1979; KURZ 1985, 1986; KOLENDOWICZ 2003, 2005), and the results of the studies conducted by CHANGNON (1985, 2001), WALKNER (1992) and KOLENDOWICZ (1998) pertaining to the analysis of a greater number of violent storms.